Altered prefrontal correlates of monetary anticipation and outcome in chronic pain. Issue 8 (August 2018) - Martucci, Katherine T.; Borg, Nicholas; MacNiven, Kelly H.; Knutson, Brian; Mackey, Sean C.
Abstract : Abstract: Chronic pain may alter both affect- and value-related behaviors, which represents a potentially treatable aspect of chronic pain experience. Current understanding of how chronic pain influences the function of brain reward systems, however, is limited. Using a monetary incentive delay task and functional magnetic resonance imaging (fMRI), we measured neural correlates of reward anticipation and outcomes in female participants with the chronic pain condition of fibromyalgia (N = 17) and age-matched, pain-free, female controls (N = 15). We hypothesized that patients would demonstrate lower positive arousal, as well as altered reward anticipation and outcome activity within corticostriatal circuits implicated in reward processing. Patients demonstrated lower arousal ratings as compared with controls, but no group differences were observed for valence, positive arousal, or negative arousal ratings. Group fMRI analyses were conducted to determine predetermined region of interest, nucleus accumbens (NAcc) and medial prefrontal cortex (mPFC), responses to potential gains, potential losses, reward outcomes, and punishment outcomes. Compared with controls, patients demonstrated similar, although slightly reduced, NAcc activity during gain anticipation. Conversely, patients demonstrated dramatically reduced mPFC activity during gain anticipation—possibly related to lower estimated reward probabilities. Further, patients demonstrated normal mPFC activity to reward outcomes, but dramatically heightened mPFC activity to no-loss (nonpunishment) outcomes. In parallel to NAcc and mPFC responses, patients demonstrated slightly reduced activity during reward anticipation in other brain regions, which included the ventral tegmental area, anterior cingulate cortex, and anterior insular cortex. Together, these results implicate altered corticostriatal processing of monetary rewards in chronic pain. Abstract : Supplemental Digital Content is Available in the Text.Decreased reward anticipation and increased no-loss outcome medial prefrontal cortex response in fibromyalgia suggests reduced monetary reward expectation and increased relief to avoided punishment, respectively.